UTILIZAÇÃO DE NANOPARTÍCULAS DE CLOREXIDINA COMO ALTERNATIVA DE MEDICAÇÃO INTRACANAL - Vitalis, Graciela Schneider (2012)
Intracanal medication aims to eliminate micro-organisms present within the system of canals, making the repair of tissues damaged by microbial action. Despite the numerous drugs used, there is not an ideal drug. This study aimed to develop and characterize nanoparticles containing chlorhexidine. Furthermore, it aimed to evaluate its degradation when associated to calcium hydroxide, and to analyze their performance in vitro and in vivo. Solid lipid nanoparticles containing chlorhexidine were developed and characterized in concentrations of 0.2 and 0.5 % chlorhexidine (suspension and gel), showing average particle size values of 88.5 nm and 84.6 nm, respectively. The samples were stored for 90 days and remained stable at 5°C and room temperature, but unstable at 40°C. The free chlorhexidine concentration reduced in 33% when associated to calcium hydroxide after 14 days of analysis. O the other hand, nanoencapsulated chlorhexidine degraded only 10 % at the same conditions. The agar diffusion test against C. albicans and E. faecalis, for 72 h, showed smaller zone of inhibition but they increased size. Despite this seemed unfavorable, the MIC result showed equal values for chlorhexidine in free form and in nanoparticles. To verify the penetration of nanoparticles in the dentin tubules, SEM/EDS was used, through the identification of chlorine atoms, allowing the observation of nanoparticles in the interior of dentin tubules and deposited on the dentin surface. In the in vivo test using rats, it was able to observe, histologically and radiographically, the effect of the lipid nanoparticles, including when associated to calcium hydroxide, improving the antimicrobial properties of the association. These results suggest that chlorhexidine can be associated to solid lipid nanoparticles, keeping its antimicrobial effect, enabling its use as intracanal medication in dentistry, and assisting in the preservation of the drug when in association with calcium hydroxide paste to avoid their degradation by high pH value.